Berglund and McCullough on mastering Cassandra for architects - McCullough, Matthew (Matthew J.); Berglund, Tim.; Safari eBooks ([S.l.] : O'Reilly Media, 2012)
"This in-depth video training session introduces you to the Cassandra NoSQL database, from drivers to deployment. Through a series of group exercises, you'll discover several new data modeling patterns in Cassandra that depart from the relational tradition in important ways. Learn how Cassandra delivers on its promise of horizontal scalability and fault tolerance, and how its log-structured storage subsystem helps it achieve impressive write and read performance. You'll also look at some common administrative scenarios such as adding and removing nodes."--Resource description page.
Title and publication information from resource description page (viewed July 18, 2012).
Presenters, Matthew McCullough, Tim Berglund.
Keywords: Cassandra (Computer file); Distributed databases; Database management; Open source software; Electronic books